Cropping systems on root rot and soybean seed yield - Maier,Maira (2018)
ABSTRACT: Root rot (RR), which can occur in different cropping systems, affects soybean seed yield. The aim of this study was to determine the incidence of RR in soybean crop systems and its relationship with soybean yield. The study was carried out for two growing seasons in a no-till system consisting of four soybean crop systems: soybean-oat+soybean-oat, soybean-maize+soybean-maize, soybean-wheat+soybean-wheat and soybean-pasture+soybean-pasture. Data were submitted to Pearson’s correlation. Incidence of RR, mainly charcoal rot and sudden death, was more than 50% in soybean roots for all the soybean crop systems and consequently decreased yield by around 22kg ha-1 of seed for every 1% increase in RR. Root rot led to a decline in seed yield from 20 to 102kg ha-1 in the first season and 9 to 32kg ha-1 in the second season, considering all the cropping systems. Soybean + pasture was the lowest productive system, with a negative RR impact of 74.9 and 32.9kg ha-1 in the first and second season, respectively.